Tallage-at-Will in Later Medieval England*. (8th March 2019) - Bailey, Mark
Abstract: Tallage-at-will was a seigniorial tax on unfree tenants and hereditary serfs in medieval England, and one of the two main tests of villeinage under the common law. Contemporary lawyers argued that it was compulsory and uncertain, which has led many historians to portray it as a variable, exorbitant and arbitrary component of villein rent, but this article offers the first comprehensive survey of its form, operation and significance. It reveals that by c .1300 the frequency and level of tallage had become codified and largely fixed, it existed in various forms, it was not found on many manors, and methods of determining individual contributions varied. Thus the example of tallage-at-will serves to reinforce the heterogeneity of villeinage in England and, by extension, the unevenness of its experience on the ground. The absence of tallage-at-will from a sizeable minority of manors c .1300, and its rapid decline and disappearance after 1348–9 from many more, raises questions about its significance as one of the two key tests of villeinage in the common law. Finally, the differences between villein tallage and free aid are explored, and found to be less clear-cut than medieval lawyers would have us believe.